Elektronske lastnosti mejnih plasti v heterostrukturah ZnSe/GaAs(001) - Bratina, Gvido (Vakuumist, 1996)
ZnSe-GaAs(001) heterostructures are one of the staple systems in novel solid-sate blue lasers. Electronic properties in these heterovalent interfaces are likely to depend on the microscopic interface environment. We have show that ZnSe-GaAs(001) heterojunction valence band offset can be tuned in the range from 0.4 eV to 1.2 eV by controling the composition of the interface through variations in the composition of the growing front. Se-rich growth conditions yield Se-rich interfaces with the resulting low value of theband offset. Zn-rich growth conditions yield Zn-rich interfaces with the resulting high value of the band offset.
Keywords: laserji; mejne plasti; elektronske lastnosti